Advances in MOF-enabled food preservation and packaging: A critical review of structure-function relationships, functionalization strategies, applications, and safety - Yinghua Tang; Yuqin Feng; Xuefeng Liu; Kuiran Liu; Wenhua Mu; Yating Song; Yuqing Duan; Guishan Liu (Food Research International, 2026)

Electrospun nanofiber interfaces for aquatic products preservation: spoilage microenvironments, molecular interactions, and mechanism-oriented design strategies - Kuiran Liu; Yuqin Feng; Xuefeng Liu; Yinghua Tang; Wenhua Mu; Yating Song; Yuqing Duan; Guishan Liu (Food Bioscience, 2026)

Sustainable bio-aerogels for food packaging applications: Fabrication strategies, preservation mechanisms, and innovation trends - Xuefeng Liu; Yuqin Feng; Yating Song; Jiajun Guo; Kuiran Liu; Yinghua Tang; Wenhua Mu; Jianfang Li; Yuqing Duan; Guishan Liu (Food Research International, 2026)

Functional interaction between Bacillus velezensis D103 and maize reveals a microbial mechanism for drought stress mitigation via photosynthesis and sugar metabolism - Yating Zhang; Zhenqiang Feng; Yanling Guo; Yingfeng An; Zhiyong Zhang; Xinyue Bi; Bo Zhang; FangFang Yu; Tong Bi; Faryal Babar Baloch; Jianjia Miao; Yunjiao Wang; et al. (Plant Science, 2026)

Warm-humid synergy aggravates thermal thaw slumping on permafrost slopes - Yongbin Wang; Mingli Zhang; Zhi Wen; Desheng Li; Yating Zhang; Zhixiong Zhou; Wei Feng (Cold Regions Science and Technology, 2026)

Unraveling the size-dependent toxicity mechanisms of polystyrene microplastics on coral symbiotic Symbiodiniaceae: Integrated physiological and transcriptomic perspectives - Jiayuan Liang; Yating Yang; Tianyi Niu; Zhicong Li; Zhuqing Liang; Mingyao Lu; Li Zhang; Yihe Feng; Sanqiang Gong; Kefu Yu (Marine Pollution Bulletin, 2026)

The dominant role of amylose content in regulating the multiscale structure of hydroxypropyl distarch phosphate for 3D printing ice cream - Minghao Xu; Yating Xu; Shengyang Ji; Yonghao Liu; Diyi Zhang; Lin Feng; Yinliang Wu; Peng Zhang; Jianfu Shen; Baiyi Lu (Food Hydrocolloids, 2026)

A standardized saltwater intrusion risk index for estuaries in the United States - Yuxun Li; Song Feng; Yating Gao; Wei Huang (Journal of Hydrology, 2026)

Circadian Rhythm Disorder-Related Dysfunctions are Exacerbated by Aging and Ameliorated by Time-Restricted Feeding - Fengjiao Huo; Qing Liu; Shuaishuai Zhang; Xiaorui Liu; Shuyao Lv; Meili Zhao; Yue Liu; Xiaoqi Zhu; Ce Huang; Shengyu Feng; Hao Wang; Siling Xu; et al. (Neuroscience Bulletin, 2026)

Using machine learning to deeply analyze the critical role of trace element additives in anaerobic digestion and guide the optimization of addition strategies - Yating Yu; Yi Zhang; Yijing Feng; Zheng Hao Leong; Junting Pan; Jianping Su; Yeqing Li (Water Research, 2026)

7,8-Dihydroxyflavone ameliorates bone loss by regulating TRKB/AKT/FOXO3a pathway in a mouse model of alzheimer’s disease - Dong Liu; Xiaoxiong Li; Peng Shi; Wenjuan Hong; Jie Huang; Mingliang Hou; Linqiu Ma; Qirong Liao; Hongyan Yang; Xiaoyan Fu; Huadong Zhou; Jing Lu; et al. (Psychopharmacology, 2025)

Copper isotopic compositions of surface sediment in the Yangtze Estuary and East China Sea Shelf - Daqian Zhang; Jincun Liu; Lian Zhou; Qian Wang; Lanping Feng; Jinhua Liu; Yating Hu; Thomas J. Algeo (Chemical Geology, 2025)

Interactions between raw dark tea chemistry and dominant fungi shape Hei brick tea quality - Yating Guo; Haijing Cui; Xinxin Wang; Haowei Guo; Xinyu Feng; Anran Yan; Yani Pan; Lixin He; Liping Liu; Kexin Zhang; Hua Fang; Hesham R. El-Seedi; et al. (International Journal of Food Microbiology, 2025)

Diversification of Alpine Soil Animals Corroborates Uplifts and Environmental Changes of Qinghai‐Tibetan Plateau and Himalayas: Insights From Molecular Phylogeny and Cryptic Diversity of the Isotoma quadridentata Complex (Collembola: Isotomidae) - Yating Zhang; Daoyuan Yu; Huanhuan Zhang; Chen Li; Yuting Jiang; Feng Zhang; Feng Hu; Manqiang Liu (Zoologica Scripta, 2025)
The Qinghai‐Tibetan Plateau and Himalayas (QTPH) are biodiversity hotspots crucial for understanding alpine speciation. While studies have focused on flora and aboveground fauna, the impact of QTPH uplift on soil fauna diversification remains understudied. To address this research gap, we investigated a representative taxon of alpine soil animals, the Isotoma quadridentata species complex (Collembola, Isotomidae) widespread at 2300–5100 m above sea level across the QTPH. On a molecular aspect, we sequenced 2 mitochondrial (COI, 16S) and 3 nuclear (18S, 28S D1–2, 28S D7–10) markers from 79 individuals representing different populations of this complex and related species. Based on these data, our single‐locus (ABGD, ASAP) and multi‐locus (single‐rate and multi‐rate mPTP) species delimitation analyses supported 11–15 candidate species among this complex. On a morphological aspect, colour patterns varied both between and within the candidate species, suggesting caution in their use for Isotoma diagnosis. Macrochaetotaxy was largely consistent, except in AG4, which showed a distinct pattern on the head. Macroevolutionary analyses indicated a Himalayan origin for QTPH Isotoma 5.88–10.25 million years ago (Mya), with the I. quadridentata complex originating in the adjacent Emei Mountain later. This complex diversified initially in the Emei Mountain before dispersing to the northeast QTPH and back to Himalayas 3.82–6.48 Mya, followed by further speciation. These findings link the origin and diversification of QTPH Isotoma and the I. quadridentata complex to the uplift of the QTPH and subsequent environmental changes since Miocene, supporting a potential impact of this geological event on the diversification of alpine soil fauna.

Electromagnetic wave-based technology for ready-to-eat foods preservation: a review of applications, challenges and prospects - Yuxin Zhang; Zhiming Ma; Jiaxin Chen; Zhongshuai Yang; Yue Ren; Jing Tian; Yuanlv Zhang; Mei Guo; Jiajun Guo; Yating Song; Yuqin Feng; Guishan Liu (Critical Reviews in Food Science and Nutrition, 2025)

Copper isotope signatures during red earth weathering and their significance for soil reticulation (Xuancheng, South China) - Daqian Zhang; Lian Zhou; Thomas J. Algeo; Ke Yin; Lanping Feng; Yu Jiao; Yating Hu; Jinhua Liu; Hanlie Hong (Geoderma Regional, 2025)

Targeted capture of Bacillus thuringiensis using phage endolysin cell wall binding domain with high recognition specificity - Qin Peng; Lushuang Wang; Gege Feng; Xi Chen; Dan Li; Yating Zeng; Yingqi Qian; Zhirou Sun; Yihui Yuan (Chemical Engineering Journal, 2025)

Linking gut microbiome profiles and white matter integrity to social behavior in young autistic children: from the perspective of individual variation - Xinyue Huang; Weixing Zhao; Rui Feng; Yuanyue Zhou; Jia Wang; Jinming Xiao; Lei Li; Xiaolong Shan; Yu Feng; Yating Ming; Jing Cao; Xiaodong Kang; et al. (Science Bulletin, 2025)

Extensive pH stability of emulsion with homogeneous esterification citrate agarose: Construction, stabilization mechanism and controlled release for bioactive - Xiaoyan Zhao; Feng Jiang; Yating Ding; Lipeng Du; Qiong Xiao; Fuquan Chen; Yonghui Zhang; Huifen Weng; Qiuming Yang; Anfeng Xiao (Food Hydrocolloids, 2025)

Preparation of porous sustainable adsorbent and its adsorption behavior for Pb2+ - Yuhang Guo; Xiao Chen; Xiaoping Feng; Mingyang Zhao; Yating Pan; Kai Zhang; Jinhui Li (Environmental Research, 2025)

Enhancing soil labile organic matter through oilseed rape-rice rotation and straw returning in paddy-upland systems - Shuntao Zhang; Tao Ren; Yating Fang; Jian Zhao; Jun Zhu; Wen-feng Cong; Hans Lambers; Jianwei Lu (Plant and Soil, 2025)

Solar interfacial evaporation based on bio-aerogel materials: A review - Ying Zhang; Jiehui Li; Yuhang Gao; Pu Feng; Yuan Deng; Jinmei He; Yating Zhang; Mengnan Qu (Desalination, 2025)

Grazing and Enclosure Alter the Vertical Distribution of Bacterial Communities in Different Microhabitats of Wetlands Along the Xilin River - Xiaoai Cao; Yating Tian; Huamin Liu; Hongbo Yu; Feng Niu; Rui Zhang; Zhichao Xu; Yi Zhuo; Lu Wen; Dongwei Liu; Lixin Wang (Wetlands, 2025)

Synergies of air pollution control policies: A review - Tong Feng; Yating Shi; Xiaomin Wang; Xudong Wan; Zhifu Mi (Journal of Environmental Management, 2025)

Characterization, expression and interactive proteins analysis of BjuB022815 in B. juncea - Jing Zeng; Li Feng; Shiyan Liu; Yating Liang; Lixia Huang (Acta Physiologiae Plantarum, 2025)

Innovative electromagnetic wave assisted freezing (EWAF) for improving frozen food quality: Principles, influencing factors, modelling, applications, and prospects - Yilin Wang; Yue Ren; Yuxin Zhang; Zhongshuai Yang; Zhiming Ma; Jiaxin Chen; Xintong Chen; Zecheng Qiu; Jing Tian; Aofei Pu; Junjie Yin; Mei Guo; et al. (Trends in Food Science & Technology, 2025)

Identification and detection of frozen-thawed muscle foods based on spectroscopy and machine learning: A review - Zecheng Qiu; Xintong Chen; Delang Xie; Yue Ren; Yilin Wang; Zhongshuai Yang; Mei Guo; Yating Song; Jiajun Guo; Yuqin Feng; Ningbo Kang; Guishan Liu (Trends in Food Science & Technology, 2025)

Probing fragile topology with dislocations - Ying Wu; Zhi-Kang Lin; Yating Yang; Zhida Song; Feng Li; Jian-Hua Jiang (Science Bulletin, 2024)

Bacterial community succession and its correlation with the dynamics of flavor compound during processing of Enshi bacon - Yating Liu; Yao Xiao; Wu Feng; Zhongyan Mo (Food Bioscience, 2024)

Optimization study on circadian tunability and Rec. 2020 of RGB-LED-based displays considering the users with different ages - Qinzhen Lin; Ruoping Lian; Haoyang Liu; Wenhui Li; Junying Li; Yating Feng; Yi Lin; Suyao Liu; Weijie Liu; Kaiyu Yang; Yinxiao Yang; Yaling Chai; et al. (Energy and Buildings, 2024)

Corrigendum to “Formation and regulation strategies for volatile off-flavor compounds in livestock meat, poultry meat, and their products: A comprehensive review” [Trends in Food Science & Technology 152 (2024) 104689] - Yue Ren; Yilin Wang; Yuxin Zhang; Zhongshuai Yang; Zhiming Ma; Jiaxin Chen; Xintong Chen; Zecheng Qiu; Jing Tian; Aofei Pu; Junjie Yin; Mei Guo; et al. (Trends in Food Science & Technology, 2024)

Enhancing urban thermal comfort during heat waves: Exploring hierarchical optimization strategies through integration of network and patch morphology - Yifeng Ji; Zhitao Li; Yating Chang; Tao Feng (Sustainable Cities and Society, 2024)

Opportunities beyond net-zero CO2 for cost-effective greenhouse gas mitigation in China - Yating Kang; Peipei Tian; Kuishuang Feng; Jiashuo Li; Klaus Hubacek (Science Bulletin, 2024)

The role of carbon price signal in green innovation: Evidence from China - Tong Feng; Xiaomin Wang; Yating Shi; Qiang Tu (Journal of Environmental Management, 2024)

Formation and regulation strategies for volatile off-flavor compounds in livestock meat, poultry meat, and their products: A comprehensive review - Yue Ren; Yilin Wang; Yuxin Zhang; Zhongshuai Yang; Zhiming Ma; Jiaxin Chen; Xintong Chen; Zecheng Qiu; Jing Tian; Aofei Pu; Junjie Yin; Mei Guo; et al. (Trends in Food Science & Technology, 2024)

Pathways and contributions of sulfate reducing-bacteria to arsenic cycling in landfills - Lifang Hu; Feng Huang; Yating Qian; Tao Ding; Yuzhou Yang; Dongsheng Shen; Yuyang Long (Journal of Hazardous Materials, 2024)

Hydrophobic sisal cellulose paper-based TENG for collecting rain energy and raindrop-based sensor - Yating Pan; Ming Li; Yuxiang Lu; Manli Lu; Bin Guo; Xianming Liu; Kaiyou Zhang; Yu Wang; Liang Feng; Aimiao Qin (Chemical Engineering Journal, 2024)

Oilseed rape-rice rotation with recommended fertilization and straw returning enhances soil organic carbon sequestration through influencing macroaggregates and molecular complexity - Shuntao Zhang; Tao Ren; Wen-Feng Cong; Yating Fang; Jun Zhu; Jian Zhao; Rihuan Cong; Xiaokun Li; Jianwei Lu (Agriculture, Ecosystems & Environment, 2024)

Recent progress of Lycium barbarum polysaccharides on intestinal microbiota, microbial metabolites and health: a review - Yuqin Feng; Yating Song; Jie Zhou; Yuqing Duan; Tianyu Kong; Haile Ma; Haihui Zhang (Critical Reviews in Food Science and Nutrition, 2024)

A versatile CuCo@PDA nanozyme-based aptamer-mediated lateral flow assay for highly sensitive, on-site and dual-readout detection of Aflatoxin B1 - Xu Zhu; Jing Tang; Xilian Ouyang; Yibo Liao; Haopeng Feng; Jiangfang Yu; Li Chen; Yating Lu; Yuyang Yi; Lin Tang (Journal of Hazardous Materials, 2024)

Environmental fate and risk evolution of calcium channel blockers from chlorine-based disinfection to sunlit surface waters - Qian Yin; Yuefei Ji; Yating Guo; Kyriakos Manoli; Wenzheng Chen; Lei Zhang; Xin Yu; Mingbao Feng (Water Research, 2024)

Diversity variation of zooplankton and phytoplankton communities in ship ballast water during the maiden voyage - Wei Feng; Qiong Wang; Yating Chen; Jian Wang; Chong Guo; Huixian Wu (Regional Studies in Marine Science, 2024)

Zirconium and neodymium isotopes record intensive felsic volcanism in South China region during the Permian-Triassic boundary crisis - Yu Jiao; Lian Zhou; Thomas J. Algeo; Lanping Feng; Jun Shen; Yating Hu; Jinhua Liu; Yan Han; Xin Hou (Chemical Geology, 2023)

Bloom forming species transported by ballast water under the management of D-1 and D-2 standards—Implications for current ballast water regulations - Yating Chen; Junzeng Xue; Wei Feng; Jiansen Du; Huixian Wu (Marine Pollution Bulletin, 2023)

Evaluate the compliance of ballast water management system on various types of operational vessels based on the D-2 standard - Wei Feng; Yating Chen; Tao Zhang; Junzeng Xue; Huixian Wu (Marine Pollution Bulletin, 2023)

OsFKBP42b Regulates Rice Growth and Development Through Interacting with OsABCB1 and OsABCB14 - Di Wang; Yingjie Wang; Gen Pan; Yanyan Wang; Guizhi Wang; Wenjing Chen; Yating Feng; Xi Liu (Journal of Plant Biology, 2023)

Riemerella anatipestifer Endonuclease I displays enzymatic activity and is associated with bacterial virulence - Ruyu Shen; Yang Yu; Zongchao Chen; Min Zhu; Yating Feng; Pengfei Niu; Shengqing Yu (Veterinary Microbiology, 2023)

Spatiotemporal changes of extreme climate indices and their influence and response factors in a typical cold river basin in Northeast China - Yating Ren; Feng Zhang; Chunli Zhao; Dongni Wang; Jiapeng Li; Jingjing Zhang; Zhiqiang Cheng (Theoretical and Applied Climatology, 2023)

MYOCD is Required for Cardiomyocyte-like Cells Induction from Human Urine Cells and Fibroblasts Through Remodeling Chromatin - Xiangyu Zhang; Lijun Chen; Xingnan Huang; Huan Chen; Baomei Cai; Yue Qin; Yating Chen; Sihua Ou; Xiaoxi Li; Zichao Wu; Ziyu Feng; Mengying Zeng; et al. (Stem Cell Reviews and Reports, 2022)

Identification and management of GCK-MODY complicating pregnancy in Chinese patients with gestational diabetes - Yanyan Jiang; Fusong Jiang; Ming Li; Qingkai Wu; Chenming Xu; Rong Zhang; Mingqiang Song; Yanzhong Wang; Ying Wang; Yating Chen; Juan Zhang; Xiaoxu Ge; et al. (Molecular and Cellular Biochemistry, 2022)

Identification of Ala2Thr mutation in insulin gene from a Chinese MODY10 family - Juan Zhang; Yanjun Liu; Ming Li; Xiaoxu Ge; Ying Wang; Xin Huang; Di Yang; Rong Zhang; Yating Chen; Ming Lu; Jun Yin; Mingqiang Song; et al. (Molecular and Cellular Biochemistry, 2020)

Arg913Gln of SLC12A3 gene promotes development and progression of end-stage renal disease in Chinese type 2 diabetes mellitus - Rong Zhang; Langen Zhuang; Ming Li; Juan zhang; Weijing Zhao; Xiaoxu Ge; Yating Chen; Feng Wang; Niansong Wang; Yuqian Bao; Limei Liu; Yanjun Liu; et al. (Molecular and Cellular Biochemistry, 2018)

Cloning and transcription analysis of the nitrate reductase gene from Haematococcus pluvialis - Lu-lu Hou; Feng Liu; Xiaonan Zang; Xuecheng Zhang; Bangxiang He; Yating Ding; Xinwei Song; Dongfang Xiao; Haitao Wang (Biotechnology Letters, 2017)

Identification of QTLs with additive, epistatic, and QTL × environment interaction effects for the bolting trait in Brassica rapa L. - Yating Liu; Chengyu Li; Xingxing Shi; Hui Feng; Yugang Wang (Euphytica, 2016)

Identification and validation of a major QTL controlling the presence/absence of leaf lobes in Brassica rapa L. - Yugang Wang; Xuejun Liu; Xiaohong Ji; Lei Zhang; Yating Liu; Xixi Lv; Hui Feng (Euphytica, 2015)